(untitled) (Al-Academy, 2017)
This research revolves around the theme (aesthetic valuer out viewer in baroque painting ) the research contains four chapters of the research go as follows: The first chapter contains the problem of the research and contains the importance and aim of the research and The limits and The first chapter ends with the definition of the terminologies . The second chapter deals with a theoretical background . It includes two sections : The first , study aesthetic valuer out viewer and The second section , study aesthetic valuer out viewer in baroque painting . The third chapter includes five samples from baroque painting . The fourth chapter includes the results of this study . also the deducements , recommendations, suggestions .Finally, the study ends, list of appropriator, and addenda.